2001
DOI: 10.1007/bf02722027
|View full text |Cite
|
Sign up to set email alerts
|

Sister-chromatid exchange analysis on long-term benzathine penicillin for secondary prophylaxis of rheumatic fever

Abstract: A single intra-muscular injection of 1.2 millions units of benzathine penicillin every 4 weeks is the most widely used method for the antibiotic prophylaxis of rheumatic fever. The aim of this study is to evaluate the effect of long-term benzathine penicillin on DNA in patients with rheumatic fever. Thirty children with confirmed rheumatic fever who were on the benzathine penicillin prophylaxis were enrolled in the study, and 30 similar normal children served as a control group. To detect any DNA damage, SCE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Serum penicillin concentration of 0.002−0.5 µg/mL is lethal for a majority of susceptible Gram‐positive bacteria and the concentration of 0.02 µg/mL or above was detected in more than 80% of serum samples obtained at the third week after intramuscular administration of BPG 3,12 . In previous studies, a significant increase in SCE frequency in children who were on long‐term BPG therapy for prophylaxis for RF, had been shown 4 . It was also confirmed by comet assay method in another study 5 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Serum penicillin concentration of 0.002−0.5 µg/mL is lethal for a majority of susceptible Gram‐positive bacteria and the concentration of 0.02 µg/mL or above was detected in more than 80% of serum samples obtained at the third week after intramuscular administration of BPG 3,12 . In previous studies, a significant increase in SCE frequency in children who were on long‐term BPG therapy for prophylaxis for RF, had been shown 4 . It was also confirmed by comet assay method in another study 5 .…”
Section: Discussionmentioning
confidence: 92%
“…Despite its common use, there is no comprehensive report on the genotoxic effect of BPG in the literature. Recently, an increased frequency of SCE was detected in children with rheumatic fever (RF) who are on long‐term BPG prophylaxis, suggesting that these changes may be due to long‐term BPG therapy or the underlying disease 4 . The findings, indicating some level of DNA damage, were then supported by comet assay 5 .…”
mentioning
confidence: 99%
“…A second reason is that antibiotics (penicillin and streptomycin) were used in the present study, but not in the previous one (Li et al, 1998). It has been reported that penicillin and streptomycin significantly increase the baseline number of SCEs in human lymphocytes from 6.50 ± 0.39 to 8.02 ± 0.39 (Das and Sharma, 1983) and from 5.82 ± 1.40 to 7.54 ± 1.81 of SCEs/cell (Dundaroz et al, 2001). A third possible reason is that the culture conditions were different between the two papers.…”
Section: Discussionmentioning
confidence: 67%
“…Using the sisters chromatid exchange method, mutagenetic and carcinogenic potentials of different substances were examinated [16,17,[20][21][22][23][24][25]. Antibiotics and non-steroidal anti-inflammatory drugs (NSAIDs) were just some of the most investigated subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Also the metabolites of Amoxicillin do not have a significant effect on cell proliferation [20]. Benzathine penicillin G (BPG) might also be considered as the "safe" antibiotic for a short-term ex posure [23], although in cases of a long-time exposure, SCE frequency changes might be expected [24]. Non-steroidal anti-inflammatory drugs (NSAIDs) include variety of chemicals with analgesic, antipyretic and anti-inflammatory effects [16].…”
Section: Discussionmentioning
confidence: 99%